Pelatihan Pembuatan Bahan Manipulatif Origami untuk Simetri Lipat dan Simetri Putar pada Bangun Datar - Asriati, Weni Widya; Julia, Nur Tri; Sari, Tesi Kumala; Danis, Amir; Jayanti, Agus; Marthin, Marthin; Marissayu, Marissayu; Rambe, Rohimah (Jurnal Pengabdian Masyarakat Bhinneka, 2025)
This training aims to enhance teachers' understanding of the concepts of line symmetry and rotational symmetry through the creation of manipulative materials using origami. The activity is conducted as an innovative solution to help students grasp mathematical concepts in a more enjoyable and accessible way. Through a practical and interactive approach, participants are guided to create and use origami as a visual and hands-on learning tool. Using manipulative materials made from origami paper can make math learning more engaging, encouraging students to be more enthusiastic and actively involved. It fosters a fun learning environment and helps students better understand the material. Moreover, this method has proven effective in strengthening students’ understanding of geometric concepts in an enjoyable and applicable manner.